FRONTLINE: Journalism as a research discipline - Chris Nash (Asia Pacific Network, 2013)
This article reviews recent debate about the performance and impact of the Excellence for Research in Australia (ERA) evaluations in 2010 and 2012 on the field of journalism research, in particular discussion of the relationship between research in journalism and that in the fields of communication, media and cultural studies. In response to that discussion and the initiation of the Frontline section in this journal (Bacon, 2012; Abplanalp, 2012; Gooch, 2012; Fitzgerald, 2013) it strongly argues that journalism is a distinct field of academic research practice. It identifies and briefly canvasses a range of methodological issues arising from Stuart Adam’s (1994) characterisation of journalism research as addressing the real, the present and the public (p. 13), and issues arising from shifting technologies and editorial/peer review processes. It indicates a range of methodological literature in cognate disciplines that can be used to ground journalism as a distinct research practice among the humanities and arts disciplines.